2008
DOI: 10.1542/peds.2007-2762
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplementing Pregnant and Lactating Mothers Withn-3 Very-Long-Chain Fatty Acids on Children's IQ and Body Mass Index at 7 Years of Age

Abstract: This study suggests that maternal concentration of n-3 very-long-chain polyunsaturated fatty acids during pregnancy might be of importance for later cognitive function, such as sequential processing, although we observed no significant effect of n-3 fatty acid intervention on global IQs. Neonatal fatty acid status had no influence on BMI at 7 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
158
1
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(176 citation statements)
references
References 42 publications
6
158
1
8
Order By: Relevance
“…In this study, the co-authors did not find significant differences in intelligence between the intervention and control groups (Campoy et al, 2011). The explanation offered was that the positive effect of prenatal supplementation may have been overshadowed by other important factors (not all of which it is possible to control for) including social stimulation, other nutrients taken, diet as a whole, illnesses, and drugs prescribed by the age of 6-7 years (Helland et al, 2008). Makrides et al (2010) conducted a well-designed multicenter double-blind randomized controlled trial in Australia on 2399 women between 2005 and 2009 from 21 weeks of gestation until birth and did not find any difference on the Bayley Scales of Infant and Toddler Development at the age of 18 months between intervention (supplemented with 800 mg DHA) and control groups (supplemented with vegetable oil capsules), after adjustment for potential confounders.…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 62%
See 3 more Smart Citations
“…In this study, the co-authors did not find significant differences in intelligence between the intervention and control groups (Campoy et al, 2011). The explanation offered was that the positive effect of prenatal supplementation may have been overshadowed by other important factors (not all of which it is possible to control for) including social stimulation, other nutrients taken, diet as a whole, illnesses, and drugs prescribed by the age of 6-7 years (Helland et al, 2008). Makrides et al (2010) conducted a well-designed multicenter double-blind randomized controlled trial in Australia on 2399 women between 2005 and 2009 from 21 weeks of gestation until birth and did not find any difference on the Bayley Scales of Infant and Toddler Development at the age of 18 months between intervention (supplemented with 800 mg DHA) and control groups (supplemented with vegetable oil capsules), after adjustment for potential confounders.…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 62%
“…However, in a follow-up study conducted at the age of 7, there was no difference in overall IQ between supplemented versus non-supplemented children, but a positive correlation was observed between the concentration of α-linolenic acid (ALA) and DHA in maternal plasma phospholipid and performance on the Sequential Processing scale (Helland et al, 2008). A possible explanation of these findings is that by 7 years of age cognitive development is influenced by many other intervening factors, and the test battery used in the research may not have been sensitive enough to detect the association between diet and cognition at this later age (Helland et al, 2008). The results of a study reported by Judge et al (2007) also supported the findings of the previous study, providing evidence that maternal DHA supplementation results in better problem solving ability (speed of processing) in 9 month old infants on the Infant Planning Test, but not on recognition memory evaluated using the Fagan Test of Infant Intelligence.…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the evidence from RCTs is inconsistent. Maternal supplementation with 803 mg EPA þ 1183 mg DHA from 18 weeks of gestation to 3 months postpartum was associated with improved child cognitive function at 4 years, but not at 3 , 6 months or 7 years (Helland et al, 2001(Helland et al, , 2003(Helland et al, , 2008, and supplementation of 8-10-year-old children with 200 mg EPA þ 83 mg DHA for 16 weeks had no effect on cognitive function (Kirby et al, 2010). Even among 6-10-year-old children potentially at-risk of poor nutrition living in urban Jakarta, supplementation for 12 months with 22 mg EPA þ 88 mg DHA was not effective in enhancing cognitive function (Osendarp et al, 2007).…”
Section: Session 2 Benefits Of Essential Fats For Future Healthmentioning
confidence: 99%